Keanekaragaman Hayati Tumbuhan Obat Tradisional dan Pemanfaatanya - Tanda Nauli Sitorban; Euis Nursaadah; Ariefa Primairyani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to analyze the diversity of medicinal plants that are still used by the Rejang tribe of Bengkulu as medicine. This research method is descriptive and quantitative. The object of this research is the types of traditional medicinal plants used by the Rejang tribe and the research subjects are battra or shamans who use Rejang tribe medicinal plants with 2 samples in each district. The data collection technique was carried out in three stages, namely the observation, interview and documentation stages. The results of the research show that there are 38 types or species of medicinal plants used by the Rejang tribal battra and 32 families. Leaves are the most commonly used part with a percentage of 58%. The main processing is by boiling, namely 62%, and most medicinal plants are consumed directly with a percentage of 67%. In conclusion, the Rejang tribe has extensive knowledge about the use of medicinal plants in traditional medicine. They know various types of medicinal plants from many different families. The use of this medicinal plant is mainly to treat ulcers, fever, coughs and cancer, and is an integral part of the culture and knowledge of the Rejang tribe. Keywords: Battra, Biodiversity, Rejang Tribe, Medicinal plants, Traditional